2020
DOI: 10.3941/jrcr.v14i5.3971
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Epipericardial Fat Necrosis on multimodality imaging in a pediatric patient: a case report and review of the literature

Abstract: This is a case report of a 13-year-old male, presented to the Emergency Department complaining of a sudden onset left-sided pleuritic chest pain for 1 day. He was found to have a mass in the left Epipericardial fat with fat stranding and pleural effusion supporting the diagnosis of Epipericardial Fat Necrosis. The findings were established by Computed tomography and Ultrasound, and the final diagnosis was confirmed by Magnetic resonance imaging. Subsequently, the patient was discharged on analgesia; reassessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The age at which EFN occurs remains unknown [4]; however, it is observed in both men and women and has been reported in children and patients with a transplantation history [5,6]. The most common symptom of EFN is chest pain; other associated symptoms include shortness of breath, dizziness, tachycardia, and cold sweats, although fever and myalgia are not considered classic clinical symptoms [3,7]. Barreto et al [8] reported that EFN with cough and fever was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The age at which EFN occurs remains unknown [4]; however, it is observed in both men and women and has been reported in children and patients with a transplantation history [5,6]. The most common symptom of EFN is chest pain; other associated symptoms include shortness of breath, dizziness, tachycardia, and cold sweats, although fever and myalgia are not considered classic clinical symptoms [3,7]. Barreto et al [8] reported that EFN with cough and fever was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology remains unclear, but hypotheses include hemorrhage owing to destruction of vulnerable vessels by Valsalva maneuvers, such as anger and breath-holding, or acute ischemia of the epicardial fat owing to tortuosity of the vascular stalk [5,9,10]. Another risk factor is the increase in pericardial fat due to obesity, which remains unknown because of the lack of case series [3,5]. Although no characteristic findings have been reported on blood samples, electrocardiograms, or chest radiographs, mild increases in the C-reactive protein level, D-dimer level, and white blood cell counts were reported [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) Epipericardial fat necrosis usually presents as a newonset pleuritic chest pain in young healthy patients. (8,9) einstein (São Paulo). 2023;21:1-5…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(13) Typical physical examination findings include tachycardia, tachypnea, and even cardiac friction rub can be found. (8) Potentially serious conditions may be related to these manifestations, such as pericarditis, pneumothorax, pulmonary embolism, acute coronary syndrome, and acute aortic syndrome. (14,15) Epipericardial fat necrosis rarely manifests as electrocardiogram changes (eventually nonspecific repolarization findings).…”
Section: ❚ Case Reportmentioning
confidence: 99%